2018
DOI: 10.1016/j.cobeha.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of females does not increase variability in rodent research studies

Abstract: The underrepresentation of female subjects in animal research has gained attention in recent years, and new NIH guidelines aim to address this problem early, at the grant proposal stage. Many researchers believe that use of females will hamper research because of the need for increased sample sizes, and increased costs. Here I review empirical research across multiple rodent species and traits that demonstrates that females are not more variable than males, and that for most traits, female estrous cyclicity ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
213
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(229 citation statements)
references
References 46 publications
11
213
2
3
Order By: Relevance
“…Other female offspring were assessed for distinct behavioural phenotypes in adulthood for a separate study. We did not assess oestrous cycle during these tasks; however, previous work has shown that variability across the cycle is not sufficiently substantial to change the interpretability of several phenotypes . The testing occurred over two cohorts: the first cohort included one to two pups from 20 litters and the second cohort included five to six pups from four litters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other female offspring were assessed for distinct behavioural phenotypes in adulthood for a separate study. We did not assess oestrous cycle during these tasks; however, previous work has shown that variability across the cycle is not sufficiently substantial to change the interpretability of several phenotypes . The testing occurred over two cohorts: the first cohort included one to two pups from 20 litters and the second cohort included five to six pups from four litters.…”
Section: Methodsmentioning
confidence: 99%
“…We did not assess oestrous cycle during these tasks; however, previous work has shown that variability across the cycle is not sufficiently substantial to change the interpretability of several phenotypes. 36 The testing occurred over two cohorts: the first cohort included one to two pups from 20 litters and the second cohort included five to six pups from four litters. There were no significant differences between cohorts in total litter size or any of the behaviour measures (all P > 0.10) and were therefore analysed together.…”
Section: Dopamine-related Behaviour Tasksmentioning
confidence: 99%
“…We can hypothesize that the reasons contributing to the bias in preclinical research [64][65][66][67] are also, at least partially, the same for human studies as well. For instance, the misconception about the increased female 66,68,69 variability-often argued because of the fluctuating sex 64 hormones-and the misguided assumption that the biological sex does not influence the function of the central nervous system are among them, especially in the fields of neuroscience and psychiatry. 65 In addition, human brain samples are difficult samples to collect in big numbers, 53 especially from psychiatric patients.…”
Section: Human Studiesmentioning
confidence: 99%
“…There was no correlation with estrus cycle phase and behavioral performance, demonstrating that hormonal fluctuations throughout the cycle did not affect the cognitive outcomes measured here. In line with these data, there are several reports demonstrating that there is commonly no requirement for increasing sample size to incorporate females and furthermore no need to account for estrus cycle phase unless that is the focus of the study [39][40][41][42].…”
Section: Discussionmentioning
confidence: 83%